α-type-1 polarized dendritic cell-based vaccination in recurrent high-grade glioma: a phase I clinical trial - Akiyama Yasuto; Oshita Chie; Kume Akiko; Iizuka Akira; Miyata Haruo; Komiyama Masaru; Ashizawa Tadashi; Yagoto Mika; Abe Yoshiaki; Mitsuya Koichi; Watanabe Reiko; Sugino Takashi; et al. (BMC Cancer, 2012)
Abstract Background High-grade gliomas including glioblastoma multiforme (GBM) are among the most malignant and aggressive of tumors, and have a very poor prognosis despite a temozolomide-based intensive treatment. Therefore, a novel therapeutic approach to controlling recurrence is needed. In the present study, we investigated the effect of activated dendritic cell (DC) (α-type-1 polarized DC)-based immunotherapy on high-grade glioma patients with the HLA-A2 or A24 genotype. Methods Nine patients with recurrent high-grade gliomas including 7 with GBMs who fulfilled eligibility criteria were enrolled into a phase I study of monocyte-derived DC-based immunotherapy. HLA-genotyping revealed 1 case of HLA-A*0201 and 8 cases of A*2402. Enriched monocytes obtained using OptiPrepTM from leukapheresis products on day1, were incubated with GM-CSF and IL-4 in a closed serum-free system, and activated on day6 with TNF-α, IL-1β, IFN-α, IFN-γ, and poly I/C. After pulsing with a cocktail of 5 synthetic peptides (WT-1, HER2, MAGE-A3, and MAGE-A1 or gp100) restricted to HLA-A2 or A24 and KLH, cells were cryopreserved until used. Thawed DCs were injected intradermally in the posterior neck at a dose per cohort of 1.0, 2.0 and 5.0× 107/body. Results The frequency of CD14+ monocytes increased to 44.6% from 11.9% after gradient centrifugation. After a 7-day-incubation with cytokines, the mean percentage of DCs rated as lin-HLA-DR+ in patients was 56.2 ± 19.1%. Most DCs expressed high levels of maturation markers, co-stimulatory molecules and type-1 phenotype (CD11c+HLA-DR+) with a DC1/2 ratio of 35.6. The amount of IL-12 produced from activated DCs was 1025 ± 443 pg/ml per 105 cells. All 76 DC injections were well tolerated except for transient liver dysfunction with grade II. Six patients showed positive immunological responses to peptides in an ELISPOT assay, and positive skin tests to peptide-pulsed DC and KLH were recognized in 4 cases. The clinical response to DC injections was as follows :1 SD and 8 PD. Interestingly, the SD patient, given 24 DC injections, showed a long-term recurrence-free and immunological positive response period. Conclusions These results indicate peptide cocktail-treated activated α-type-1 DC-based immunotherapy to be a potential therapeutic tool against recurrent high-grade glioma with mainly HLA-A*2402. Trial registration Current non-randomized investigational trial UMIN-CTR UMIN ID: 000000914.